MARKETING U SPORTSKOJ INDUSTRIJI - Igor Radošević; Šandor Reperger (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Sports industry prezents a biznis where sports protagonists are holding a central place: atleths, coaches, managers, sports organizations and organizers of sports events as unigue promoters of corperative biznis, sponsors and overall sports audiance wich they possess. During last hundred years, development of tehnique and tehnology, science and education, market and comunications, people's high standard enlarge fundamental to unnecesseary needs. Today, the world is "overcrowded" with the new products and services. Everything is offering, creating spending mentality. The manufecturers are scrambling for consumers, they are not afried and they are taking there money offering mostly unnecesary products, and consumer, happy that can choose is strikeing into the consumers "feever". To work and to spent becomes the meaning of life, the money becomes fetish - the blessed thing that helps consumer to create his ilusions and fantasys, to satisfay his needs and instincts, to replace his basic modest with blantacy. As soon as sport began to make sucses, rezults and services, to fulfill a wide selection of men's needs, it's necessarily becomes a need of sport for managment and marketing. Today, sport is a serios economic activity, the market that implicate a billion active athlets and two billion that passively accompany sports events trought the mass media. Billions of dollars are flocking in to the sport enlarging his mission and helping his furder expansion.